Cybercrime and Digital Transformation - V. P. Kirilenko; G. V. Alekseev (Теоретическая и прикладная юриспруденция)
Cyberspace crime is a critical threat to the information security of the state and civil society institutions. Inside global network the abuse of computer user’s trust allows organized criminal groups to achieve their economic and political goals by committing offenses in the international information space. The methods of participatory observation, comparative legal and discourse analysis show that digital transformation has weakened the influence of the state on the development of the cultural sphere of society, and computer technologies have become the object of interests of criminal structures. Digital transformation has created virtual reality based on the laws and regulations of the networked community. Civil society by rejecting most of the peremptory norms imposed by national governments for political purposes produce victims of a wide range of cybercrimes: fraud and computer misuse offences and obscene publications. Since digital transformation is a universal phenomenon that will inevitably change the life of the entire world community, it is necessary to reach a consensus on the development and implementation of modern international agreement which, on the one hand, will guarantee freedom of speech and the right of every person to access information, and on the other hand will protect citizens, states and social institutions from criminal encroachments in an actively developing digital environment.